Diastolic Dysfunction Following Acute Myocardial Infarction with ST Segment Elevation - Imelda Krisnasari; Anna Fuji Rahimah; Sasmojo Widito; Cholid Tri Tjahjono (Universitas Brawijaya, 2022)
ST segment elevation myocardial infarction (STEMI) caused by atherosclerotic vulnerable plaque rupture or plaque erosion, resulting in activation of the coagulation cascade. It causes a temporal sequence known as the “ischemic cascade,” which first involves the metabolic process, the diastolic dysfunction, and then systolic dysfunction. Diastolic dysfunction in STEMI patient is an independent predictor for long-term outcome. Rapid and early restoration of blood flow is critical to ensure cell recovery and prevent additional damage.